Following in our footsteps: how adult demonstrations of literacy and numeracy can influence children's spontaneous play and improve learning outcomes. Issue 8 (3rd August 2018) - Colliver, Yeshe; Arguel, Amaël
ABSTRACT: Play is traditionally considered the foundation of learning in the early years. Because play is characterized by free choice, it can be difficult for adults to ensure all learning is useful for children. The intervention described here took a novel approach to this problematic. It exposed 17 four-year-olds to different adult demonstrations to see if they influenced what children were interested to play with. It was theorized that by demonstrating certain problem-solving activities to children over four weeks, value would be ascribed to these literacy or numeracy activities and children would play with them. In doing so, they would learn literacy and numeracy skills. Results indicate that children exposed to numeracy demonstrations played significantly more with numeracy concepts, and those exposed to literacy demonstrations improved on reading measures. What children are exposed to may influence their interests and learning. Implications for early childhood education and parenting are discussed. GRAPHICAL ABSTRACT: